Enhancing Seventh-Grade Numeracy Skills in Data Presentation Through Interactive Gaming - Hans Juwiantho; Alycia Jane Sidarta (IJECA (International Journal of Education and Curriculum Application), 2024)
Integrating educational content into a game format aims to make learning more enjoyable and accessible to students. The game’s design focuses on gradually increasing the difficulty level to challenge students’ abilities and encourage problem-solving. The benefit of this numeracy game for learning is its ability to create a lively and interactive learning environment. By immersing students in a captivating storyline and providing opportunities for exploration and discovery, the game fosters engagement and enthusiasm for learning. The game offers immediate feedback to players, allowing them to learn from their mistakes and improve their skills over time. Moreover, the game is a supplementary tool for educators to reinforce classroom learning and provide additional practice opportunities for students. It encourages independent learning and critical thinking while reinforcing mathematical concepts in a fun and interactive way. Survey results consist of 21 seventh-grade students from various schools, indicating high engagement, with 95.2% finding the game stimulating. The pre-test and post-test have 5 questions covering various mathematical concepts relevant to numeracy skills; the questions addressed topics such as pie charts, graphs, tables, logical reasoning, and drawing conclusions from given data. The result scores show improvement, rising from 2/5 to 3.43/5, suggesting a learning process during gameplay.